Chronic pruritus associated with dermatologic disease in infancy and childhood: Update from an interdisciplinary group of dermatologists and pediatricians. Issue 6 (27th August 2013) - Metz, Martin; Wahn, Ulrich; Gieler, Uwe; Stock, Philippe; Schmitt, Jochen; Blume‐Peytavi, Ulrike
Abstract: An effective treatment strategy for chronic pruritus in children with dermatologic disorders should consider the multidimensional aspects of pruritus, the unique challenges associated with treating pruritic skin disorders in the pediatric population, and evidence‐based therapies with demonstrated antipruritic benefits and clinically relevant effects on patient/family quality of life (QoL). The Course of Advanced Learning for the Management of ITch (CALM‐IT) Task Force is an interdisciplinary group of experts specializing in core aspects of pruritus treatment, integrating pediatrics, dermatology, psychotherapy, pruritus management, and sleep. CALM‐IT recently convened to provide updated guidance on managing chronic pruritus associated with dermatologic diseases in pediatric patients, with a special focus on atopic dermatitis (AD) and chronic spontaneous urticaria (csU). This review highlights the updated concepts and best practices, which were built upon international PRACTALL consensus and modified for children and infants with AD and csU. CALM‐IT supports the routine use of basic skin therapy and the escalation of topical medications, according to severity and focused on rapid itch control. Anti‐inflammatory agents should be appropriate for infants and children (i.e., with an optimized therapeutic index) and have proven antipruritic properties, such as those demonstrated by methylprednisolone aceponate. New experimental findings do not support the use of non‐sedating oral antihistamines as adjuvant antipruritic therapy for AD. In csU, oral H1 ‐antihistamine use is justified, consistent with the distinct pathophysiologic mechanisms of itch underlying AD and csU. All encompassing QoL assessments should consider the burden of both patient and caregiver and should address outstanding unmet clinical needs of pediatric patients. Future research areas include integrated QoL assessments and multidisciplinary treatment programs with pediatric‐targeted pruritic therapies providing rapid itch control.